Magnetic Attachment Retained Complete Overdenture as Treatment for Maintaning Alveolar Ridge Height – A case report - Angdrijono, Anita; Herdijantini, Nike; Eka, Hanoem (Indonesian Journal of Dental Medicine, 2018)
Background:  Magnetic attachment can be used as  a retentive devices in overdenture technique in prostheses. The magnets are attached with remaining root structure transfer the occlusal load to the bone through the periodontal ligament of retained roots and then prevent resorption of the  alveolar ridge. Alvelar ridge plays an important role for the retention and stability of the denture as they will support the denture base. Magnetic assembly consist of magnet and coping with a keeper on the remaining tooth structure  since magnetic attachment can provide support, stability and retention. Purpose: The purpose of this case report was to report magnetic attachment retained complete overdenture design and fabrication as a preserve to alveolar bone height to achieve retention and stability of the denture.  Case: A 69 years old female patient, a baker and private English teacher with partial edentulous ridge came to Dental Hospital of Airlangga University asked for dentures. Clinical examination shown a complete edentulous in the upper jaw and partial edentulous in the lower jaw. The remaining teeth were 33, 34, 35, 43 and 44. 33 and 35 are chronic gangrene radix, 35 shown a slightly mobility. 34 non vital, 44 and 45 are vital with moderate resorption. Case management : All the left teeth in the lower jaw were consulted for endodontic treatment. Magnetic attachment retained complete overdenture was choosen for the lower jaw and complete denture for the upper jaw. The remaining teeth in the lower jaw kept the alveolar ridge from resorption and the magnet provided extra retention for the complete overdenture. Discussion: Overdentures supported by magnet attachment achieved greater satisfaction, gives better retention  and stability for the denture. On the other side, the natural abutment teeth in overdentures  preserved  better proprioception and psychologically beneficial as the patient had not undergone extraction. As a conclusion, overdenture supported by magnetic attachment can be used to increase support, retention and stability especially in the lower jaw and also  prevent further alveolar ridge resorption. Conclusion: Overdenture supported by magnetic attachment can be used to increase retention and the residual root also prevent further alveolar ridge resorption.